A possible new activator of PI3K‐Huayu Qutan Recipe alleviates mitochondrial apoptosis in obesity rats with acute myocardial infarction. Issue 12 (13th May 2022) - Tai, He; Tong, Yu‐jing; Yu, Rui; Yu, You; Yao, Si‐cheng; Li, Ling‐bing; Liu, Ye; Cui, Xiao‐zheng; Kuang, Jin‐song; Meng, Xian‐sheng; Jiang, Xiao‐lin
Abstract: Obesity, which has unknown pathogenesis, can increase the frequency and seriousness of acute myocardial infarction (AMI). This study evaluated effect of Huayu Qutan Recipe (HQR) pretreatment on myocardial apoptosis induced by AMI by regulating mitochondrial function via PI3K/Akt/Bad pathway in rats with obesity. For in vivo experiments, 60 male rats were randomly divided into 6 groups: sham group, AMI group, AMI (obese) group, 4.5, 9.0 and 18.0 g/kg/d HQR groups. The models fed on HQR with different concentrations for 2 weeks before AMI. For in vitro experiments, the cardiomyocytes line (H9c2) was used. Cells were pretreated with palmitic acid (PA) for 24 h, then to build hypoxia model followed by HQR‐containing serum for 24 h. Related indicators were also detected. In vivo, HQR can lessen pathohistological damage and apoptosis after AMI. In addition, HQR improves blood fat levels, cardiac function, inflammatory factor, the balance of oxidation and antioxidation, as well as lessen infarction in rats with obesity after AMI. Meanwhile, HQR can diminish myocardial cell death by improving mitochondrial function via PI3K/Akt/Bad pathway activation. In vitro, HQR inhibited H9c2 cells apoptosis, improved mitochondrial function and activated the PI3K/Akt/Bad pathway, but effects can be peripeteiad by LY294002. Myocardial mitochondrial dysfunction occurs following AMI and can lead to myocardial apoptosis, which can be aggravated by obesity. HQR can relieve myocardial apoptosis by improving mitochondrial function via the PI3K/Akt/Bad pathway in rats with obesity.